Eastward radiation of C4 crops from the Hongshan culture core region initiated around 6 ka - Licheng Guo; Qiaowen Zhang; Shiling Yang; Shangfa Xiong; Zihua Tang; Zhe Liu; Jingyi Cui; Linlin Cui (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Cyclic response of severely damaged subway station central columns repaired with ECC jackets under highly variable axial loads - Jia Yang; Peng Deng; Chao Zhang; Renpeng Chen; Shiling Pei (Engineering Structures, 2026)

The role of orbital obliquity in modulating Pliocene warm period climate: An assessment using idealized extreme experiments - Xiaofang Huang; Shiling Yang; Alan Haywood; Julia Tindall; Minmin Sun; Xiaoxiao Yang; Hongmei Li; Wenying Jiang (Global and Planetary Change, 2026)

Large-scale vegetation deterioration in response to mid-Holocene cooling across China's Hengduan Mountains - Wenying Jiang; Xiaoxiao Yang; Xiaofang Huang; Lingyu Tang; Enlou Zhang; Shiling Yang (Global and Planetary Change, 2026)

Pickering emulsions stabilized by bovine bone gelatin - xanthan gum conjugates: an effective carrier for curcumin encapsulation - Mingfeng Sun; Wenxia Wu; Huanhuan Yang; Mou Zhao; Xiang Zhou; Nengmao Chen; Jingtao Sun; Shiling Lu; Qingling Wang; Juan Dong (Food and Bioproducts Processing, 2026)

Mechanistic insights into electric-field-induced ice suppression and ion migration in ice-channel-confined NaClO4 electrolyte - Zhenyu Zhang; Dejun Xiong; Zizhen Yan; Yang Guo; Heng Zhang; Shiling Yuan (Chemical Engineering Journal, 2026)

Enantioselective metabolic mechanism and metabolism pathway of tetraconazole in human liver microsomes: In vitro and in silico study - Shiling Liu; Junqi Zhu; Yu Wang; Wenyu Dai; Ya Zhou; Tengfei Zhang; Xianzhang Yang; Jingjing Wu; Yanmei Liu; Jie Luo; Huihua Tan; Feng Zhao (Environmental Pollution, 2026)

Seismic fragility of segmental tunnels with optimal pairs of intensity measure and engineering demand parameter - Jiaxing Zhou; Zihan Yang; Chao Zhang; Zhixiong Lang; Peng Deng; Ze Chen; Shiling Pei; Renpeng Chen (Soil Dynamics and Earthquake Engineering, 2026)

Ultrasound-assisted phosphorylation-modified sunflower meal protein: characterization and evaluation as a polyphenol delivery system - Zeliang Qi; Jiaxin Jin; Haojuan Chen; Jinsong He; Yazhi Liu; Haotian Cui; Yi Yang; Shiling Lu; Juan Dong; Qingling Wang (Journal of Food Engineering, 2026)

Promotion of CeO2 in Mn3O4-CeO2 composite towards the catalytic oxidation of Butyl acetate - Fuding Tan; Peng Liu; Yahao Liu; Shiling Yang; Xiaoju Lin; Xiaoliang Liang; Steven L. Suib; Daiqi Ye (Journal of Environmental Sciences, 2026)

Vascular normalization by erianin unleashes CAR-T immunotherapy in glioblastoma - Shiling Zhou; Shuyi Qian; Bowen Sun; Peng Shi; Shanni Guo; Changrui Yang; Jiwei Zhang; Yanqing Gong; Fan Yang (Angiogenesis, 2026)

Globally synchronous acceleration of soil formation approximately 12,000 years ago - Licheng Guo; Qiaowen Zhang; Haozhong Xue; Shangfa Xiong; Shiling Yang; Zihua Tang; Linlin Cui; Jingyi Cui; Yongda Wang; Shihao Zhang (Global and Planetary Change, 2026)

Preparation and characterization of modified sunflower meal protein–quercetin nanoparticles: Shelf–life study of seasoned lamb kebabs - Jinsong He; Jiaxin Jin; Haojuan Chen; Zeliang Qi; jinling Wang; Xiaomeng Wei; Yi Yang; Shiling Lu; Juan Dong; Qingling Wang (Food Chemistry, 2026)

Enhanced degradation of carbamazepine in water by a chitosan-supported tea polyphenols/nano-zero-valent iron system: Mechanistic insights and toxicological risk assessment - Weiwei Yu; Yuanxin Liu; Jianglin Tan; Yue Liang; Jiang Hu; Qing Tu; Shuo Yang; Ji Li; Sikai Zhao; Yang Liu; Xinyan Li; Yan Luo; et al. (Journal of Cleaner Production, 2025)

The xylem anatomical structure, physiological characteristics and aromatic components analyses explain the difference of fungal solution induced agarwood formation in Aquilaria sinensis - Shengjiang Pang; Weiwei Zhao; Guihua Huang; Qingbin Jiang; Zaizhi Zhou; Qingqing Zhang; Zuwei Tian; Pei Zhang; Zhongguo Li; Shuokun Deng; Shiling Liu; Baoguo Yang (Trees, 2025)

Juvenile hormone signaling regulates apoptosis mediated chlorantraniliprole sensitivity in Spodoptera frugiperda (Lepidoptera: Noctuidae) - Jie Luo; Huili Ouyang; Shiling Liu; Haiyan Wu; Faqian Xiong; Taiyi Yang; Honghong Li; Xuesheng Li (Pesticide Biochemistry and Physiology, 2025)

Vegetation dynamics and carbon isotope responses to the early eocene hyperthermals - Peizong Lü; Zuoling Chen; Yongli Lu; Shiling Yang; Zihua Tang; Zhongli Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Co-adjustment of chitosan-based film structure by pH and anthocyanin concentration for the development of reshness-indicating labels on chilled mutton - Mou Zhao; Huanhuan Yang; Cenchen Ran; Ziyi Liao; Zihang Zhai; Jingtao Sun; Shiling Lu; Hua Ji; Juan Dong (Food Chemistry, 2025)

High-precision U–Pb geochronology of the Guttenberg Carbon Isotope Excursion (GICE) recorded in the Tarim Basin, NW China - Junjie Xu; Jahandar Ramezani; Huaichun Wu; Qiang Fang; Jinghui Guo; Shiling Yang; Shihong Zhang; Tianshui Yang; Zhuyin Chu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Recycling of flotation residual carbon from coal gasification fine slag through thermal combustion reaction: Insight into the spatial and temporal multi-scale evolution of typical heavy metals - Yang Guo; Jianjun Wu; Fanhui Guo; Yixin Zhang; Shiling Yuan; Chunan Du; Juan Chen; Meng Lin (Fuel, 2025)

Synergistic catalysis of dual-sites promoted cycloaddition of CO2 with epoxides - Shiling Zhao; Kaizhi Wang; Beibei Yang; Zehui Sun; Yu Zhao (Fuel, 2025)

Gelatin/polyvinyl alcohol films loaded with doubly stabilized clove essential oil chitosomes: Preparation, characterization, and application in packing marinated steaks - Cenchen Ran; Qingqing Li; Mou Zhao; Haotian Cui; Yi Yang; Kui Diao; Yazhi Liu; Shiling Lu; Juan Dong; Qingling Wang (Food Chemistry, 2024)

Selective hydrogenation of biphenyl to cyclohexylbenzene over Cu based catalysts - Shiling Zhao; Kaizhi Wang; Beibei Yang; Yu Zhao; Jingxuan Cai (Chemical Engineering Journal, 2024)

Identification of climatic tipping points and transitions in Chinese loess grain-size records utilizing nonlinear time series analysis - Haozhong Xue; Song Song; Mengfan Qiu; Xiaofang Huang; Shiling Yang; Zihua Tang (Quaternary International, 2024)

Pliocene CO2 rise due to sea-level fall as a mechanism for the delayed ice age - Shiling Yang; Yongda Wang; Xiaofang Huang; Minmin Sun; Jingtai Han; Xu Wang; Zuoling Chen; Shihao Zhang; Wenying Jiang; Zihua Tang; Zhaoyan Gu; Shangfa Xiong; et al. (Global and Planetary Change, 2024)

Molecular insights into the adsorption and penetration of oil droplets on hydrophobic membrane in membrane distillation - Shideng Yuan; Xin Yang; Na Zhang; Jiaojiao Zhang; Shiling Yuan; Zhining Wang (Water Research, 2024)

UBE2J1 promotes ALV-A proviral DNA synthesis through the STAT3/IRF1 signaling pathway - Xingming Wang; Shiling Zheng; Chun Fang; Xiongyan Liang; Yuying Yang (Veterinary Microbiology, 2024)

Origin and depositional background of the Holocene black soil in Northeast China: Evidence from grain-size analysis and optically stimulated luminescence dating - Shihao Zhang; Shiling Yang; Shangfa Xiong; Licheng Guo; Yongda Wang; Xiaofang Huang; Minmin Sun; Zhongli Ding (CATENA, 2024)

Enhanced east–west climatic contrast in northern China under past global warming: Evidence from paleovegetation records and numerical simulations - Xiaofang Huang; Shiling Yang; Wenying Jiang; Minghu Ding; Yongda Wang; Minmin Sun; Shihao Zhang (Quaternary Science Reviews, 2023)

Palynology-based reconstructions for climatic patterns in the Eocene–Oligocene of eastern Asia: Implications of the monsoonal circulation history - Song Song; Zihua Tang; Dangpeng Xi; Shiling Yang (Journal of Asian Earth Sciences, 2023)

Correction to: Effects of Dl-3‑n‑butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effects of Dl-3-n-butylphthalide on cognitive functions and blood–brain barrier in chronic cerebral hypoperfusion rats - Yang Ma; Shiling Chen; Yuanwei Li; Jiahui Wang; Jingfei Yang; Jie Jing; Xia Liu; Yunjie Li; Jingyi Wang; Ping Zhang; Zhouping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Vascular cognitive impairment (VCI) has been one of the major types of cognitive impairment. Blood–brain barrier damage plays an essential part in the pathogenesis of VCI. At present, the treatment of VCI is mainly focused on prevention, with no drug clinically approved for the treatment of VCI. This study aimed to investigate the effects of DL-3-n-butylphthalide (NBP) on VCI rats. A modified bilateral common carotid artery occlusion (mBCCAO) model was applied to mimic VCI. The feasibility of the mBCCAO model was verified by laser Doppler, 13 N-Ammonia-Positron Emission Computed Tomography (PET), and Morris Water Maze. Subsequently, the Morris water maze experiment, Evans blue staining, and western blot of tight junction protein were performed to evaluate the effect of different doses of NBP (40 mg/kg, 80 mg/kg) on the improvement of cognitive impairment and BBB disruption induced by mBCCAO. Immunofluorescence was employed to examine the changes in pericyte coverage in the mBCCAO model and the effect of NBP on pericyte coverage was preliminarily explored. mBCCAO surgery led to obvious cognitive impairment and the decrease of whole cerebral blood flow, among which the blood flow in the cortex, hippocampus and thalamus brain regions decreased more significantly. High-dose NBP (80 mg/kg) improved long-term cognitive function in mBCCAO rats, alleviated Evans blue leakage and reduced the loss of tight junction proteins (ZO-1, Claudin-5) in the early course of the disease, thereby exerting a protective effect on the blood–brain barrier. No significant changes in pericyte coverage were observed after mBCCAO. High-dose NBP improved cognitive function in mBCCAO rats. High-dose NBP protected the integrity of BBB by upregulating TJ protein expression, rather than regulating pericyte coverage ratio. NBP could be a potential drug for the treatment of VCI.

Response of East Asian summer monsoon to precession change during the mid-Pliocene warm period - Xiaofang Huang; Shiling Yang; Alan Haywood; Julia Tindall; Dabang Jiang; Yongda Wang; Minmin Sun; Shihao Zhang (Quaternary International, 2023)

BrGDGTs-based temperature and hydrological reconstruction from loess-paleosol deposits in the Eastern European Plain since 200 ka - Shihao Zhang; Shiling Yang; Wenying Jiang; Xiaofang Huang; Yongda Wang; Minmin Sun; Licheng Guo; Xiaoxiao Yang; Zhongli Ding (Quaternary Science Reviews, 2023)

Freshwater ecosystem collapse and mass mortalities at the Paleocene-Eocene thermal maximum - Zuoling Chen; Zhongli Ding; Jimin Sun; Shiling Yang; Xijun Ni; Xu Wang; Yongli Wang; Jiangyong Zhang; Wei He (Global and Planetary Change, 2023)

Microbial degradation of petroleum characteristic pollutants in hypersaline environment, emphasizing n-hexadecane and 2,4 di-tert-butylphenol - Shiling Liu; Wenjiao Yuan; Xiaolin Yang; Chengbin Li; Yishan Ji; Xin Feng; Meitong Li; Yuhong Xie (Environmental Monitoring and Assessment, 2023)

Total organic carbon content as an early warning indicator of soil degradation - Licheng Guo; Shangfa Xiong; Yulu Chen; Jingyi Cui; Shiling Yang; Heng Wang; Yongda Wang; Zhongli Ding (Science Bulletin, 2023)

Simulations reveal causes of inter-regional differences in Pliocene climatic periodicity - Xiaofang Huang; Shiling Yang; Alan Haywood; Julia Tindall; Dabang Jiang; Yongda Wang; Minmin Sun; Shihao Zhang; Zhongli Ding (Science Bulletin, 2023)

Changes in Cerebral Blood Flow and Diffusion-Weighted Imaging Lesions After Intracerebral Hemorrhage - Jingfei Yang; Jie Jing; Shiling Chen; Xia Liu; Yingxin Tang; Chao Pan; Zhouping Tang (Translational Stroke Research, 2022)

The East Asian Monsoon since the Last Glacial Maximum: Evidence from geological records in northern China - Shiling Yang; Xinxin Dong; Jule Xiao (Science China Earth Sciences, 2019)

Antioxidant effect of hawk tea extracts on camellia oil oxidation during microwave heating - Zhou Xu; Xu Li; Shiling Feng; Jing Liu; Lijun Zhou; Ruiwu Yang; Chunbang Ding (Journal of Consumer Protection and Food Safety, 2018)

Methods and application of using detrital zircons to trace the provenance of loess - Jing Xie; ShiLing Yang; ZhongLi Ding (Science China Earth Sciences, 2012)